A rare case of ciprofloxacin-induced cholestatic hepatits in the newborn - Mohamed Sellouti; Karima Laarbi Ouassou; Abdelhakim Ourrai; Amale Hassani; Rachid Abilkassem; Aomar Agadr (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2021)
Ciprofloxacin is a broad-spectrum fluoroquinolone antibiotic with wide spectrum of activity against Gram-negative, Gram-positive and anerobic organisms. It has greatest utility in the treatment of children hospitalized with serious bacterial infections. The adverse effects on the liver usually range from asymptomatic elevation of liver enzymes to fulminant hepatitis.  Ciprofloxacin has also been linked to rare cases of cholestatic jaundice that usually arises after 1 to 3 weeks of therapy. Most cases are mild and self-limited, but at least one instance of vanishing bile duct syndrome related to Ciprofloxacin therapy has been published.  We report a case of cholestasis in neonate of gestational age 35 weeks who had septicaemia and received ciprofloxacin for 8 days. This infant developed cholestasis and deranged liver transaminases several days after the discontinuation of therapy with ciprofloxacin.